Booster Cushion for Shared Mobility: The development of two new portable booster cushions - Johansson, Charlie; Simmons, Sebastian (My University, 2020)
The aim of this report was to develop one or several booster cushions suited for a future use in shared mobility. This meant the product would have to be easy to carry, easy to use, adds user and customer value and still makes the cars protective systems available for the child. A rising need for this type of booster cushion can be seen as car sharing and carpooling is becoming more and more common in everyday society. Several topics were researched to get an understanding of what value the product would imbue. By performing several interviews, a survey and several benchmarks, an understanding of the booster cushion and its usage was obtained. After this 26 concepts were created and evaluated through several elimination matrices with criteria built from a requirement specification and a customer needs list. The final concept were evaluated further through static FEM analyses and prototype observations. The primary factor for affecting portability was deemed to be the carrying feature followed by the volume, and in third place weight. Two booster cushion concepts were conceived which were capable of changing size, the AID and the SaFE. The AID is an automatically inflatable booster cushion which utilizes a drop stitch construction for increased durability and an automatic pump to increase ease of use while the inflation aspect makes it portable. The SaFE is able to compress in two dimensions, reducing in width using a sliding mechanism and in depth by a folding itself in half. A more robust and easy to use revision of the SaFE was made which also conformed to the new UN R129 regulations. Several additional features were also presented and briefly evaluated together with future recommendations which could increase the products potential further for both the AID and the SaFE. In the discussion the products and processes are discussed in detail with regards to time constraints and how different priorities could have led to different outcomes. Possible sources of errors are discussed, how they were dealt with and what could have been done differently. How the project was affected by the CoVID-19 virus pandemic is also taken into account. Finally, future development and recommendations for the SaFE and AID is discussed. In the conclusion the aims are compared to the achieved results with the AID and SaFE. While some of the aims such as ’easy to carry’ and ’easy to use’ can be considered more developed than others, all of the aims have been fulfilled in some way. However, all of the aims similarly shows potential to become more fulfilled and the report have recommendations for how to continue development.
Keywords: booster, cushion, foldable, inflatable, automatic, safety, R129; shared, mobility, future